Intimate relationships and hypnosis: insecure adult attachment affects emotions and absorption during hypnosis - Di Filippo, Gloria; Perri, Rinaldo Livio (Frontiers in Psychology, 2024)
Introduction Hypnosis research indicates that subjects are not equally hypnotizable. Most studies on hypnotizability focused on the relationships with personality or cognitive variables. At the same time, only a few proposed the contribution of the attachment style, defined as the result of the childhood relationship with the caregivers and influencing the adult relations. Methods In the present investigation, two studies were carried out to test the possible association between adult attachment and hypnotic responsivity. The adult attachment was assessed using the Experiences in Close Relationships-Revised (ECR-R) questionnaire, while hypnosis was assessed through the Harvard Group Scale of Hypnotic Susceptibility (HGSHS:A; Study 1) and the Phenomenology of Consciousness Inventory: Hypnotic Assessment Procedure (PCI-HAP; Study 2) in order to adopt a behavioral and a phenomenological approach, respectively. Results Analyses showed that attachment factors (anxiety and avoidance) were not associated with the level of hypnotizability, whereas it was associated with variations of consciousness during hypnosis, mainly internal dialogue, absorption and negative emotions. Overall, the insecure attachment styles yielded increased mind wandering and restlessness during hypnosis when compared to the secure style. The reason probably lies in the feeling of anxiety or danger of insecurely attached individuals when involved in intimate or confidential relationships. Conclusion These findings clarify a still poorly investigated aspect concerning the influence of attachment style on hypnotic experience and further highlight the need to consider inter-individual differences and the phenomenological perspective when assessing hypnosis and hypnotizability.